(untitled) (Norfolk, 2002)
This volume describes in detail the new technology necessary to study the entire genome in a holistic manner and all the high throughput and large-scale experimental methodologies currently being used in genomic science. In addition the authors describe the progress of the newest technologies that are currently being developed. Written by experts in the field, this concise yet informative volume covers all aspects of technology pertaining to genomic studies. An essential book for anyone involved in genomic science.
Keywords: Genomics,Gen